Epidemiologic and Genetic Associations of Erythropoietin With Blood Pressure, Hypertension, and Coronary Artery Disease. Issue 5 (November 2021) - Sun, Pengfei; Kumar, Nitin; Tin, Adrienne; Zhao, Jing; Brown, Michael R.; Lin, Zesen; Yang, Min-Lee; Zheng, Qiwen; Jia, Jia; Bielak, Lawrence F.; Yu, Bing; Boerwinkle, Eric; et al.
Abstract : While exogenous administration of recombinant erythropoietin has been associated with increased risk of hypertension, coronary artery disease, and mortality, it is not known if endogenous circulating erythropoietin level is associated with coronary artery disease and its risk factors. We measured and analyzed epidemiological and genetic associations of circulating plasma erythropoietin levels in 2 population cohorts, from China (N=4329) and the United States (N=3671). In vitro smooth muscle cell responses and in vivo murine studies of erythropoietin exposure were performed. Erythropoietin levels were positively and linearly associated with blood pressure traits and inversely associated with cholesterol levels and red cell indices. Higher erythropoietin level was associated with higher prevalence of hypertension (odds ratio, 1.20 [95% CI, 1.12–1.29], P =4.41×10 −7 ) and coronary artery disease (odds ratio, 1.16 [95% CI, 1.00–1.34], P =0.046). In a discovery stage genetic association study of erythropoietin level, we identified a previously reported locus on chromosome 6 (rs7776054 near HBS1L-MYB, P =4.86×10 −25 ) and a new locus on chromosome 4 (rs172629 near PDGFRA-KIT, P =2.1×10 −8 ), which was independently replicated. Meta-analysis of discovery and replication genetic association results identified a locus on chromosome 22 (rs855791 near TMPRSS6, P =3.60×10 −9 ). Erythropoietin administration, within a physiological range of hematocrit achieved, induced hypertension in vivo and increased contraction of vascular smooth muscle cells in vitro. In conclusion, endogenous circulating erythropoietin level is influenced by common genetic variation and is associated with blood pressure traits, hypertension, and coronary artery disease. Vascular effects of erythropoietin demonstrated in vitro and in vivo support a newly discovered mechanism of hypertension and cardiovascular risk with potential implications for erythropoietic support in the clinic. Abstract : Supplemental Digital Content is available in the text.